Mineralisasi pada batuan induk batugamping di daerah Lepadi, Dompu, Nusa Tenggara Barat - Herman, Danny Zulkifli (Geological Agency, 2008)
http://dx.doi.org/10.17014/ijog.vol3no3.20086Lepadi area situated in the Regency of Dompu, West Nusa Tenggara, is occupied by limestone unit comprising limestone and sandy limestones; and sandstones which are occasionally found as lenses within units of tuffaceous sand and tuff breccia. Indication of metallic mineralization is shown by the occurrence of the base metal-bearing quartz veins penetrating a host rock of limestone. A pervasive hydrothermal alteration was formed as chlorite-calcite- muskovite/sericite-quartz and kaolinite/haloysite series with veins consisting of massive quartz veinlets (millimeter to 2.0 cm maximum width) and very thick vuggy quartz veins (Â± 3.2 m width). The first quartz type contains ore minerals such as galena, sphalerite, chalcopyrite, pyrite and iron oxide; whilst the second type has a predominant galena content with an association of, chalcopyrite, covelite, pyrite and iron oxide which occurred as tiny vugs filling and distributed sporadically within the quartz body. The result of studies by using microscope (petrography and mineragraphy), infra-red analysis (PIMA), chemical analysis and fluid inclusion on entirely altered rock/ore mineral/quartz vein samples reveals that the alteration and mineralization processes might occur in a mineralization system involving hydrothermal fluid of near neutral at the temperature ranging from 275Âº - 200oC. It brings to a suggestion that deposition of quartz veins and associated ore minerals has taken place in a depth ranging from 620 â 150 m beneath paleosurface. It is based on hydrothermal fluidâs salinity ranging from 1.2 â 2.2 equivalent wt.% NaCl de- tected from fluid inclusion within quartz crystal samples. Â